"Spoiled Identity" and "The Frozen Now": Rebalancing "The Trouble" in CanLit with the Medical Conceptualization of Shame. Issue 4 (2nd October 2022) - Neilson, Shane
ABSTRACT: With a constantly evolving and newly erupting menu of scandals over the period extending from 2015 to the present, a sense of crisis has been instilled in Canadian literature. Whither CanLit? These continually unfolding scandals have pushed some scholars to respond through various attempts at inventory-taking. This article asks: are the kinds of inventory-taking the field is conducting somehow paradoxically deleterious? Is shame as an affect a productive way for processing and healing trauma? Does the current solution to unfolding scandals in the industry of Canadian literature, that of waging shame, actually preclude the resolution of scandal? Does waging shame reinforce the process of trauma itself? Is there some kind of misapprehension of shame as an affect in literary and cultural studies that might be augmented with a more medical understanding of the effects of shame on human beings? In short, what happens when shame becomes a disciplinary identity?